ШАХМАТ ТЎГАРАКЛАРИНИ ТАШКИЛ ЭТИШНИНГ ПЕДАГОГИК ВА ПСИХОЛОГИК АСОСЛАРИ - Холиқов, У.Қ. (SCIENCE and SOCIETY, 2021)
This article examines the state of chess clubs in general education schools at the same time and the process of their systematic organization. The systematic organization of chess clubs is analyzed in schools and appropriate recommendations are given. Reaching out to more students with the proposed system is scientifically proved.